2012
DOI: 10.1080/10640266.2012.668482
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Eating and Gender Identity Disorder: A Qualitative Study

Abstract: The association between disordered eating and gender identity was examined in a sample of 20 (11 female-to-male, 9 male-to-female) transgender Finnish adults, aged 21-62 years. Using semi-structured interviews, participants' own understanding of the underlying causes of their disordered eating was analyzed, as well as the effect of gender reassignment on eating behaviors and cognitions. A majority of the participants reported current or past disordered eating. Participants most frequently described strive for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
95
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 9 publications
13
95
0
1
Order By: Relevance
“…In several studies, participants described feelings of hatred or dissociation from particular aspects of their body such as breasts, hips, body fat, genitals, shoulder width, and body hair distribution (Ålgars et al, 2010;Bozkurt et al, 2006;Pfeffer, 2008). Both transmen and transwomen have reported trying to lose weight in order to suppress the development or continuation of secondary sexual characteristics (Ålgars, Alanko, Santtila, & Sandnabba, 2012;Vocks et al, 2009). Also, perfectionism, defined as "excessive personal expectations for personal achievement," was found to be highest among transgender persons compared to cisgender males or females (Khoosal et al, 2009, p. 220).…”
Section: Research On Transgender Adultsmentioning
confidence: 95%
“…In several studies, participants described feelings of hatred or dissociation from particular aspects of their body such as breasts, hips, body fat, genitals, shoulder width, and body hair distribution (Ålgars et al, 2010;Bozkurt et al, 2006;Pfeffer, 2008). Both transmen and transwomen have reported trying to lose weight in order to suppress the development or continuation of secondary sexual characteristics (Ålgars, Alanko, Santtila, & Sandnabba, 2012;Vocks et al, 2009). Also, perfectionism, defined as "excessive personal expectations for personal achievement," was found to be highest among transgender persons compared to cisgender males or females (Khoosal et al, 2009, p. 220).…”
Section: Research On Transgender Adultsmentioning
confidence: 95%
“…So far, the literature appears to suggest that body dissatisfaction plays a key role in the development of disordered eating (Ålgars et al, 2012;Khoosal et al, 2009;Silverstein et al, 1990). Within this review, five papers were identified which explored disordered eating as well as body image in trans people (see Table 2).…”
Section: Body Dissatisfaction and Disordered Eating In Trans People: mentioning
confidence: 99%
“…Out of the 26 papers which met the criteria for inclusion in this review, 18 explored the prevalence of body image in a trans population Becker et al, 2015;Bozkurt et al, 2006;Colizzi et al, 2015;De Vries et al, 2011Fisher et al, 2013Fisher et al, , 2014Fleming, MacGowan, Robinson, Spitz, & Salt, 1982;Kozee, Tylka, & Bauerband, 2012;Kraemer, Delsignore, Schnyder, & Hepp, 2007;Lai, Chiu, Gadow, Gau, & Hwu, 2010;Lindgren & Pauly, 1975;Marone, Lacoella, Cecchini & Ravenna, 1998;Pauly & Lindgren, 1976;Smith, Van Goozen, Kuiper, & Cohen-Kettenis, 2005;Steensma, McGuire, Kreukels, Beekman, & Cohen-Kettenis, 2013;Wolfradt & Neumann, 2001). Three studies explored disordered eating in trans individuals (Ålgars et al, 2012;Khoosal, Langham, Palmer, Terry, & Minajagi, 2009;Silverstein, Carpman, Perlick, & Perdue, 1990). Five papers related to both disordered eating and body image and explored the prevalence of these constructs (Ålgars et al, 2010;Cella, Iannaccone, & Cotrufo, 2013;Witcomb et al, 2015;Vocks, Stahn, Loenser, & Legenbauer, 2009;Wiseman & Moradi, 2010).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations